Comparison between a new platelet count drop method PL-11, light transmission aggregometry, VerifyNow aspirin system and thromboelastography for monitoring short-term aspirin effects in healthy individuals. (February 2015) - Guan, Jie; Cong, Yulong; Ren, Junwei; Zhu, Yuan; Li, Li; Deng, Xinli; Bai, Jie
Abstract Platelet function has been described by many laboratory assays, and PL-11 is a new point-of-care platelet function analyzer based on platelet count drop method, which counts platelet before and after the addition of agonists in the citrated whole blood samples. The present study sought to compare PL-11 with other three major more established assays, light transmission aggregometry (LTA), VerifyNow™ aspirin system and thromboelastography (TEG), for monitoring the short-term aspirin responses in healthy individuals. Ten healthy young men took 100 mg/d aspirin for 3-day treatment. Platelet function was measured via PL-11, LTA, VerifyNow and TEG, respectively. The blood samples were collected at baseline, 2 hour, 1 day during the aspirin treatment and 1 day, 5 ± 1 days, 8 ± 1 days after the aspirin withdrawal. Moreover, 90 additional healthy subjects were recruited to establish a reference range for PL-11. Platelet function of healthy subjects decreased significantly 2 hours after 100 mg/d aspirin intake and began to recover during 4–6 days after the aspirin withdrawal. Correlations between methods were PL-11 vs. LTA (r = 0.614, p < 0.01); PL-11 vs. VerifyNow (r = 0.829, p < 0.01); PL-11 vs. TEG (r = 0.697, p < 0.001). There was no significant bias between PL-11 and LTA at baseline (bias = 1.94%, p = 0.804) using Bland-Altman analysis, while the data of PL-11 were significantly higher than LTA (bias = 24.02%, p < 0.001) during the aspirin therapy. The reference range for PL-11 in healthy young individuals was from 66.8 to 90.5% (95%CI). When aspirin low-responsiveness was defined as LTA > 20%, the cut-off values for each method were, respectively: PL-11 > 50%, VerifyNow > 533 ARU, TEG > 60.2%. The results of different platelet function assays were uninterchangeable for monitoring aspirin response and correlations among them were also varied. Correlations among PL-11 and other three major assays suggested the ability of PL-11 to assess the treatment effects of aspirin. But a large cohort study is needed to confirm the cut-off value of aspirin response detected by PL-11.